ADVANCEMENTS IN HEART FAILURE MANAGEMENT: A COMPREHENSIVE NARRATIVE REVIEW OF EMERGING THERAPIES - Yakupboev Sherzod Ergashboy o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Furthermore, the introduction outlines the purpose of the review, which is to provide a comprehensive overview of the latest advancements in heart failure management. This includes an exploration of emerging therapies, novel treatment modalities, and promising research in the field. By shedding light on the current landscape of heart failure management and the potential future directions, this review aims to offer valuable insights for healthcare professionals, researchers, and patients alike. The introduction thus serves as a gateway to the subsequent sections of the review, laying the foundation for an in-depth exploration of the subject matter.